Multiple sclerosis – a review - Dobson, R.; Giovannoni, G. (European journal of neurology, 2019)
Multiple sclerosis (MS) is the commonest non‐traumatic disabling disease to affect young adults. The incidence of MS is increasing worldwide, together with the socioeconomic impact of the disease. The underlying cause of MS and mechanisms behind this increase remain opaque, although complex gene–environment interactions almost certainly play a significant role. The epidemiology of MS indicates that low serum levels of vitamin D, smoking, childhood obesity and infection with the Epstein–Barr virus are likely to play a role in disease development. Changes in diagnostic methods and criteria mean that people with MS can be diagnosed increasingly early in their disease trajectory. Alongside this, treatments for MS have increased exponentially in number, efficacy and risk. There is now the possibility of a diagnosis of ‘pre‐symptomatic MS’ being made; as a result potentially preventive strategies could be studied. In this comprehensive review, MS epidemiology, potential aetiological factors and pathology are discussed, before moving on to clinical aspects of MS diagnosis and management.